Perpustakaan sebagai pusat kegiatan keilmuan dan pergerakan mahasiswa dalam novel Babel - Syifa Salsabila Putri; Nina Mayesti (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. This paper investigates how the academic library's concepts, functions, and roles as the center of scholarly and student activities are portrayed in the novel Babel by R.F. Kuang. Data Collection Methods. This research used Bengtsson’s qualitative content analysis model. Data was collected through an extensive reading and found 111 data that matched with the research focus. Data Analysis. Data were analyzed through decontextualization with open coding and then recontextualized into 89 data to categorize and interpret. Results and Discussion. The library supported students by being portrayed as a learning commons, co-working space, and makerspace; hence it became the scholarly activity center for scholars. Libraries are not portrayed neutral in providing services and tend to limit students’ research scope and public access to information. The libraries are also used for non-academic activities, such as a source of magical power production and knowledge development center, the center of social and student movements. The library representation in the novel is not only a critique towards academia and its information institutions, but also an example of the library’s negative stereotype. Conclusion. From the author's perspective, the library is portrayed as a center for scholarly activities and directly involved in student political life as it becomes the center of student movements.